Expenditures on Oncology Drugs and Cancer Mortality-to-Incidence Ratio in Central and Eastern Europe - Vrdoljak, Eduard; Bodoky, Gyorgy; Jassem, Jacek; Popescu, Razvan; Pirker, Robert; Čufer, Tanja; Bešlija, Semir; Eniu, Alexandru; Todorović, Vladimir; Kopečková, Katerina; Kurteva, Galia; Tomašević, Zorica; et al. (The oncologist, 2019)
BACKGROUND: There is a steady decline in cancer mortality in Western Europe (WE), but this trend is not so obvious in Central and Eastern Europe (CEE). One of the largest discrepancies between WE and CEE is the level of investment in cancer care. The objective of our analysis was to examine the correlation between mortality-to-incidence (M/I) ratio and expenditures on oncology drugs in CEE and WE. MATERIALS AND METHODS: This cross-sectional analysis was done on publicly available data. Data on expenditures for oncology drugs were obtained from QuintilesIMS, and data on M/I ratio from Globocan. The main outcome was mortality-to-incidence ratio, and the primary analysis was performed by Spearman's rank correlation. RESULTS: There is a large discrepancy in expenditure on oncology drugs per cancer case between WE and CEE, and within CEE. Average expenditure on oncology drugs per capita as well as per new cancer case was 2.5 times higher in WE than in CEE. Availability of oncology drugs was highest in Germany (100%), relatively similar in WE (average of 91%), but in CEE it ranged from 37% to 86%, with an average of 70%. Annual expenditures on all oncology drugs per new cancer case was significantly negatively correlated with the M/I ratio (Spearman's ρ = -0.90, p < .001). CONCLUSION: There is a financial threshold for oncology drugs per cancer case needed to increase survival. Based on significantly lower expenditures for oncology drugs in CEE in comparison with WE, more investment for drugs as well as better, more organized, value- oriented consumption is needed. IMPLICATIONS FOR PRACTICE: Cancer is not treated equally successfully in Western Europe (WE) and in Central and Eastern Europe (CEE). This study showed that success in treatment of cancer is associated with the amount of money invested in oncology drugs. CEE countries spend on average 2.5 times less than WE countries for oncology drugs per new cancer case. These findings should be used by health care providers and oncologists struggling for more resources and better, more organized, evidence-based allocation of these resources as well as better oncology outcomes.
Keywords: farmakoterapie; Cross-Sectional Studies; Incidence; Europe; Evropa; incidence; Oncology; průřezové studie; Neoplasms; Drug Therapy; Humans; Central and Eastern Europe; Mortality; nádory; Health Expenditures; výdaje na zdravotnictví; Drug expenditures; lidé; Cancer